Identification of early and extra-early maturing tropical maize inbred lines with multiple disease resistance for enhanced maize production and productivity in sub-Saharan Africa - Bankole, F.; Badu-Apraku, Baffour; Salami, A.O.; Falade, Titilayo D.O.; Bandyopadhyay, R.; Ortega Beltran, A. (Scientific Societies, 2022)
Maize, a staple for millions across sub-Saharan Africa (SSA), faces major biotic constraints affecting production and safety of the crop. These include the northern corn leaf blight (NCLB), southern corn leaf blight (SCLB), Curvularia leaf spot (CLS), and aflatoxin contamination by Exserohilum turcicum, Bipolaris maydis, Curvularia lunata, and Aspergillus flavus, respectively. Farmers in SSA would benefit tremendously if high yielding maize hybrids with multiple disease resistance (MDR) were developed and commercialized. Forty-nine early-maturing (90-95 days to physiological maturity, EM) and 55 extra-early-maturing (80-85 days to physiological maturity, EEM) IITA inbred lines were identified as resistant to NCLB in field evaluations in multiple agro-ecologies of Nigeria in 2017 and 2018. From each maturity group, 30 most resistant inbreds were selected for evaluation for resistance to SCLB and CLS using a detached leaf assay. Additionally, the inbreds were screened for resistance to kernel rot and aflatoxin contamination using a kernel screening assay. Seven EM and six EEM maize inbreds were found to be highly resistant to the three foliar pathogens while ten inbreds were resistant to the foliar pathogens and supported significantly (P = 0.01) less aflatoxin accumulation than other inbreds. Inbreds having MDR should be tested extensively in hybrid combinations and commercialized. Large-scale use of maize hybrids with MDR would i) increase maize production and productivity, and ii) reduce losses caused by aflatoxin contamination. Overall, planting of EM and EEM maize hybrids with MDR would contribute to food security, reduced aflatoxin exposure, and increased incomes of maize farmers in SSA.